Lexikon des Sozialismus - Meyer, Thomas 1943- Hrsg; Heimann, Siegfried 1939- (Bund-Verl, 1986)
Thomas Meyer/Karl-Heinz Klär/Susanne Miller/Klaus Novy/Heinz Timmermann (Herausgeber): Lexikon des Sozialismus. Bund Verlag, Köln 1986, 774 Seiten, 112 DM